Analisis Kegiatan Tari Kreasi untuk Mengembangkan Motorik Kasar Anak Usia Dini di RA Miftahul Jannah Palembang - Riyani Desfira Arinda; Amir Hamzah; Tutut Handayani; Izza Fitri (Journal on Education, 2025)
The aim of this research is to find out "an analysis of creative dance activities to develop gross motor skills in early childhood at RA Miftahul Jannah Palembang". In this research the researcher used a qualitative type of case study research method. The total sample was 10 children from RA Miftahul Jannah Palembang, data collection techniques used observation, tests and documentation. The data analysis technique used in this research uses data reduction, data presentation, and drawing conclusions. The results of this observation are that creative dance activities to develop gross motor skills of young children at RA Miftahul Jannah Palembang are quite good in the movements taught by the teacher. At RA Miftahul Jannah Palembang we also follow several procedures for creative dance activities to ensure that creative dance activities run smoothly and follow existing procedures.